Global public health implications of human exposure to viral contaminated water - Lanrewaju, Adedayo Ayodeji; Enitan-Folami, Abimbola Motunrayo; Sabiu, Saheed; Edokpayi, Joshua Nosa; Swalaha, Feroz Mahomed (Frontiers in Microbiology, 2022)
The most common waterborne pathogens are enteric viruses, often found in surface waters contaminated by sewage. They gain entrance into the water environment from the discharge of raw or partially treated wastewater and are the most common cause of gastroenteritis. The World Health Organization classified waterborne viral pathogens as having high health implications and include adenovirus, rotavirus, hepatitis A and E viruses, norovirus, and other caliciviruses and enteroviruses like coxsackievirus and polioviruses. Apart from being linked with gastroenteritis, they can also be associated with diarrhea coupled with other symptoms such as fever and abdominal cramps. Furthermore, some enteric viruses have also been implicated in more severe infections such as encephalitis, meningitis, hepatitis (hepatitis A and E viruses), cancer (polyomavirus), and myocarditis (enteroviruses). Therefore, in this review, we present information on the occurrence of enteric viruses of public health importance in water and wastewater, diseases associated with human exposure to these viruses, assessment of their presence in contaminated water as well as how to prevent or remove these viruses which portends a threat to public health. In a bid to prevent the occurrence of diseases associated with human exposure to viral contaminated water, we suggested the conduction of regular viral monitoring of treated wastewater discharged into the environment. Furthermore, we highlighted the need for research to be focused on the development of a more holistic disinfection method that will inactivate waterborne viruses in water samples as this is highly needed to curtail the public health effects of human exposure to contaminated water. Moreover, such a method must be devoid of the formation of disinfection by-products which characterizes the chemical methods of disinfection owing to the possible mutagenic and carcinogenic ability of those by-products.